Combined Effects of PPARγ Agonists and Epidermal Growth Factor Receptor Inhibitors in Human Proximal Tubule Cells. (24th February 2013) - Pegg, Katherine; Zhang, Jie; Pollock, Carol; Saad, Sonia
Abstract : We aimed to determine whether epidermal growth factor receptor (EGFR) inhibition, in addition to a peroxisome proliferator-activated receptor gamma (PPAR γ ) agonist, prevents high-glucose-induced proximal tubular fibrosis, inflammation, and sodium and water retention in human proximal tubule cells exposed to normal glucose; high glucose; high glucose with the PPAR γ agonist pioglitazone or with the P-EGFR inhibitor, gefitinib; or high glucose with both pioglitazone and gefitinib. We have shown that high glucose increases AP-1 and NF κ B binding activity, downstream phosphorylation of EGFR and Erk1/2, and fibronectin and collagen IV expression. Pioglitazone reversed these effects but upregulated NHE3 and AQP1 expression. Gefitinib inhibited high glucose induced fibronectin and collagen IV, and EGFR and Erk1/2 phosphorylation and reversed pioglitazone-induced increases in NHE3 and AQP1 expression. Our data suggests that combination of an EGFR inhibitor and a PPAR γ agonist mitigates high-glucose-induced fibrosis and inflammation and reverses the upregulation of transporters and channels involved in sodium and water retention in human proximal tubule cells. Hence EGFR blockade may hold promise, not only in limiting tubulointerstitial pathology in diabetic nephropathy, but also in limiting the sodium and water retention observed in patients with diabetes and exacerbated by PPAR γ agonists.